Multi-Disciplinary Experience - A Key Learning Experience in Effective Education for Sustainable Development - Mahendra Gooroochurn; Bhoomitra Toolsy (Universitas Diponegoro, 2021)
The key role of education for achieving sustainable development has been well recognized around the world and used as a powerful lever for transforming economies based on sound principles. Indeed universities are prime institutions which have the essential role to impart requisite knowledge and skills to learners so that they can stand to the challenges in their respective professions, which means universities have had to bring radical changes to their curricula over the past decade to integrate sustainability principles as well as come up with new programmes centered on sustainability. However, the multi-disciplinary nature of sustainability projects as they occur in real-life has meant that the education curricula cannot be developed in isolation for a given programme of studies, but need to have linkages and crossover with other disciplines to provide a platform for learners to nurture this all-important skill. The University of Mauritius has aligned this key ingredient of education for sustainable development (ESD) with the accreditation framework for engineers provided by the Washington Accord through its graduate attributes, specifically Graduate Attribute 8 which includes multidisciplinary work within the range statement. This paper describes the methods adopted to implement this cross-linking between programmes from different disciplines effectively.